[3]Rotaxanes with Mixed Axles: Polyynes and Cumulenes - Franz, Michael; Januszewski, Johanna; Hampel, Frank; Tykwinski, Rik R. (European Journal of Organic Chemistry, 2019)
Tailoring synthetic strategies toward complex, but well-defined, molecular architectures is an important aspect of Today's organic chemistry. Herein, we present designs to build up [3]rotaxanes of Type 2.1 and Type 3 that feature both a polyyne and a cumulene axle in a single mechanically interlocked molecule. The combination of two sp-hybridized carbon chains was achieved by functionalization of a phenanthroline-based macrocycle, which allowed the coupling of two [2]rotaxanes toward Type 3 [3]rotaxanes with two polyynes, two cumulenes, or one polyyne and one cumulene axle. The structures have been established by NMR and UV/Vis spectroscopies, as well as high-resolution mass spectrometry. A [3]rotaxane of Type 3, featuring two [9]cumulene axles, has been assembled and spectroscopically characterized despite expectations that it would be unstable. This represents only the second cumulene rotaxane reported to date. All designs and attempts to form [3]rotaxanes of Type 2.1, which combine a polyyne and cumulene threaded through a single macrocycle, have been unsuccessful.
CRIS-Team Scopus Importer:2019-06-21
Keywords: Carbon atomic wire; Cumulenes; Mechanical bond; Polyynes; Rotaxanes